Cultivation of Willows and Poplars in Lahaul - Singh, D. P. (Indian Forester, 1950)
Lahaul-a dry tract lying above 9,000’ -has few forests and there is acute scarcity of firewood and timber. Tree growth being very slow under natural conditions we have to look forward to sources other than the so-called forests in Lahaul to meet with the existing and increasing demand of firewood and timber. Willow and poplar plantations seem to be the only practicable, effective, and immediate solution of our difficulties. Both the species can be grown without difficulty and there is considerable scope for their cultivation and extension in the Valley.